Osak-Asik (Sandiworo) sebagai Perpaduan Empat Sendratari di Era Modern - Murniati Murniati; Zahrotun Nafisah (An-Nida : Jurnal Komunikasi Islam, 2018)
This research is a cultural research. The theme is the existence of culture in Tanjung village, Pakis Aji, Jepara. This research is aimed at finding out khasanah about the existence of local culture happened in Tanjung village. This study uses an ethnoghrapy approach to find out the exixtence the Reog, Barongan, and Janggrong culture in Tanjung village. The findings of this research are: 1) The existence of Reog, Barongan, and Ketoprak culture have been started to be faded. This is because of aversing of young generatios in that village to study and practice about the cultures. Fortunaltely, there is a prominent figure who can perform Reog, Barongan, and Ketoprak; 2) whereas the Janggong culture has been lost in that village. It is because the performer of Janggong passed away. Fortunately, a gong buyut that is a tool of Janggrong is still exist until now. This tool is as an evidence of archaeological site occured in Tanjung village.